Application of DNA Barcoding in Species Identification of Pieridae Family from Entopia Penang Butterfly Farm - Ainol Azifa Mohd Faik; Lee, Jee Whu; Lee, Ping Chin; Awang Muhammmad Sagaf BakarAbu; Meng, Matthew Huan Yew; Lee, Yoke Kuen (2018)
Misidentification of butterfly species can be contributed by certain factor(s) such as mimicry, seasonal sampling (dry/wet season), cryptic and sex dimorphism. DNA barcoding is a technique used for rapid identification of butterfly species at a molecular level based on the analysis of standardized mitochondrial DNA region. A 648 base-pair of cytochrome oxidase c subunit I (COI) is highly effective in identifying vertebrate and invertebrate species. Individuals of the same species will generally have very similar COI base sequence. COI is used as a DNA barcode reference due to maternal inheritance, compact structure, lack of genetic recombination and relatively fast evolutionary rate. Therefore, it is widely used in phylogenetic and evolution studies. The DNA barcode of identified butterfly species was submitted to Barcode of Life Data System (BOLD). Thirteen species belonging to Pieridae family from Entopia Penang Butterfly Farm were chosen for this study. With reference to some samples, morphological identification method was not sufficient. There were 10 butterflies that were discovered to be different based on DNA barcoding compared to morphological identification. Triplicates of Eurema brigitta (n=3) were found to be identified as Eurema sari sodalis. Morphologically identified Eurema hecabe (n=3) were discovered as Eurema hecabe contubernalis, Eurema andersoni, and Eurema simulatrix respectively. One sample of Appias indra (n=3), was identified as Appias cardena perakana. Appias libythea (n=3) were actually identified as Appias olferna olferna. From this result, the application of DNA barcoding is indeed a useful tool in further justifying the collected butterfly species.